PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Imran Ukkas; Dirham Latif (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Abstract: In certain conditions, employees are not always be able to do the job descriptions that have been assigned by the company caused by several things, for example, employees have some obstructions caused by certain reasons. At this point, the role of OCB is very indispensable in a team work. This research aims to determine the effect of organizational climate and organizational commitment on Organizational Citizenship Behavior (OCB) to the employees of PT. PLN (Persero) Area Palopo. The research took sample 113 employees. The analysis used in this research is descriptive quantitative analysis method called equational of multiple linear regression. The result of this research showed a significant positive effect between organizational climate and organizational commitment on Organizational Citizenship Behavior (OCB) to the employees either partially or simultaneously. So this research could be a reference for PT. PLN (Persero) Area Palopo to keep improving the quality of employee’s performance through Organizational Citizenship Behavior (OCB). Keywords: Organizational Climate, Organizational Commitment, Organizational Citizenship Behavior (OCB)